93 Older adult fall prevention—getting to outcome measures in the clinical setting. (1st September 2016) - Lee, Robin; Parker, Erin; Bergen, Gwendolyn; Casey, Colleen; Eckstrom, Elizabeth; Floyd, Frank; Dellinger, Ann; Baldwin, Grant
Abstract : Background: Worldwide falls are a threat to adults 65 and older. In the United States, one in three older adults will fall annually costing the health care system 34 billion. With U.S. fall rates on the rise, and 10, 000 older adults turning 65 each day, falls are a major health threat. Description of the problem: Falls can be prevented by addressing modifiable risk factors (e.g., medication usage, vitamin D deficiency, vestibular disorders, vision deficits) with effective clinical interventions; however, few older adults talk to their health care provider about falls. Therefore, CDC launched the STEADI (Stopping Elderly Accidents, Deaths, and Injuries) initiative. STEADI uses established clinical guidelines and evidence-based interventions to empower primary care providers to screen, assess, and treat elderly patients' modifiable fall risk factors. This session describes the STEADI implementation process, key implementation steps, and subsequent health outcomes. Results: STEADI was implemented in multiple health systems. Critical in implementing STEADI was the proactive leadership of clinical champions embedded within the clinical practice; the identification of relevant quality and financial drivers; the modification of electronic health record tools; and the adoption of a STEADI clinical workflow for patients, staff, and providers that aligned with existing workflows. Preliminary measures in one setting indicate providers have screened upwards of 70 per cent of their older adult patients, and hospitalizations and emergency department visits for fall-related injuries are declining. Conclusion: Fall interventions offered in clinical settings can prevent falls among older adults, thereby improving their health, independence, and quality of life. These interventions can reduce medical costs associated with fall injuries, including hospitalisation costs for traumatic brain injuries and hip fractures. Using these data, CDC is disseminating the adoption of STEADI nationwide.